2020
DOI: 10.1108/sasbe-06-2020-0092
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy synthetic evaluation of the challenges of smart city development in developing countries

Abstract: PurposeThis study presents a fuzzy synthetic evaluation of the challenges of smart city realisation in developing countries, using Nigeria as a case study. By defining and delineating the problems faced by the country, more viable directions to attaining smart city development can be achieved.Design/methodology/approachThe study adopted a post-positivist philosophical stance with a deductive approach. A structured questionnaire was used to gather data from built environment professionals involved in the delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 65 publications
0
68
0
Order By: Relevance
“…In this section, the selected research papers are reviewed and the challenges for the three elements of digital nations are classified into six broad categories (Appendix 1 and Appendix 2) (Agarwal et al, 2017;Chauhan et al, 2016;Singh et al, 2020). The categories are based on smart city development theories and related concepts (Aghimien et al, 2020;Ali et al, 2018;Glyptis et al, 2020;Joshi et al, 2016;Rana et al, 2018;Silva et al, 2018), as well as the categories identified by other researchers (Singh et al, 2020). The challenging categories, provide the basis for building a framework for developing digital nations, and they can also be categorized as pillars if they are strengthened.…”
Section: Findings and Resultsmentioning
confidence: 99%
“…In this section, the selected research papers are reviewed and the challenges for the three elements of digital nations are classified into six broad categories (Appendix 1 and Appendix 2) (Agarwal et al, 2017;Chauhan et al, 2016;Singh et al, 2020). The categories are based on smart city development theories and related concepts (Aghimien et al, 2020;Ali et al, 2018;Glyptis et al, 2020;Joshi et al, 2016;Rana et al, 2018;Silva et al, 2018), as well as the categories identified by other researchers (Singh et al, 2020). The challenging categories, provide the basis for building a framework for developing digital nations, and they can also be categorized as pillars if they are strengthened.…”
Section: Findings and Resultsmentioning
confidence: 99%
“…By integrating blockchains, cities are expected to become able to realize sustainable targets because the technology can support several smart city sectors such as healthcare, transportation, logistics and supply chain management, and public administration. While weak citizen involvement, poor governance, and threats of system failure are the main concerns hampering the development of sustainable smart cities (Aghimien et al 2020 ), digitalization of administration, citizenship, smart city activities through blockchain can bring several advantages in terms of system transparency, security, resilience. Moreover, the alignment of blockchain with sustainability goals can help cities encounter the degradation of infrastructure and resources by supporting the development of smart applications that alleviate traffic congestion, reduce global warming, and cater to the needs of the citizens.…”
Section: Discussionmentioning
confidence: 99%
“…Closed ended questionnaires were utilised as the data-collecting instrument in this study (Aghimien et al, 2020). Kothari (2004) and Walliman (2011) agree with the use of questionnaires as a suitable, effective and efficient way of collecting quantitative data.…”
Section: Business-case Bmentioning
confidence: 94%